Tongue Hyperpigmentation Associated with Temozolomide as a Single Agent: Case Report - Gil, Lúcia Moreira (2022)
Hyperpigmentation of the tongue has been associated with chemotherapy, specifically cytotoxic drugs, but the exact pathophysiological mechanism is still not well understood. We describe a 37-year-old black woman that presented with tongue hyperpigmentation one week after the initiation of chemotherapy with temozolomide as a single agent. No cases of tongue hyperpigmentation associated with temozolomide as a single agent have been reported before. The diagnosis of drug associated pigmentary changes is based on the confirmation the onset of the clinical observations shortly after the initiation of the chemotherapy agent. The tongue hyperpigmentation is usually self-limited. This case constitutes a challenge for healthcare professionals and patients and emphasizes the importance of documenting these cases in order to guide healthcare professionals in managing the expectations of the patients and the potential adverse effects associated with certain drugs.